Method for producing aluminum-diamond composite

By adopting layered structure and aluminum alloy melt-pressure method, the processing problem of aluminum diamond composite materials is solved, rapid and economical production is achieved, and the thermal resistance and strength of the material are improved.

JP7665021B2Active Publication Date: 2025-04-18DENKA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023523422
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-26
Filing Date
2022-05-16
Publication Date
2025-04-18
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

In the prior art, it is difficult to process quickly and economically when manufacturing aluminum diamond composite materials, especially due to the high hardness of diamonds, expensive processing methods such as laser processing are required. The diamond powder on the cutting surface will affect the strength of metal coating or welding and increase thermal resistance.

Method used

A layered structure is adopted, in which the layers containing diamond powder are arranged alternately with the layers of transparent ceramic materials, and by melting and pressing the aluminum alloy into the layer structure, the aluminum diamond composite material is formed, avoiding the use of expensive methods such as laser processing.

Benefits of technology

The rapid and economical production of aluminum diamond composite materials is achieved, and the use of expensive methods such as laser processing is avoided. The thermal resistance performance and strength of the material are improved through improved layer structure and metal coating technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665021000003
    Figure 0007665021000003
  • Figure 0007665021000004
    Figure 0007665021000004
  • Figure 0007665021000005
    Figure 0007665021000005
Patent Text Reader

Abstract

One aspect of the present disclosure provides a production method for an aluminum-diamond composite that has a step for providing a layered structure that includes a composition layer that contains a diamond powder inside an opening part of a flat porous material such that the layered structure is separated from an inner circumferential surface of the opening part and a step for pressing a metal molten material that contains aluminum between the porous material and the layered structure and impregnating the composition layer with the molten material to form a composite part that contains aluminum and diamond while also forming a metal layer at at least a side surface of the layered structure, the layered structure comprising, in order, a first mold release plate, a first inorganic layer, the composition layer, a second inorganic layer, and a second mold release plate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to methods for producing aluminum-diamond based composites. [Background technology]

[0002] Aluminum-diamond composites are materials that combine diamond, which has a high thermal conductivity, and aluminum, which has a high thermal expansion coefficient, and are used for various applications such as heat sinks. In the manufacture of aluminum-diamond composites, a large-sized composite is first prepared and then processed into the product shape. However, since it contains diamond and has high hardness, it is difficult to process it with inexpensive mechanical processing. Therefore, methods such as laser processing, water jet processing, and electric discharge processing are used to manufacture aluminum-diamond composites.

[0003] When an aluminum-diamond composite is used as a heat dissipation member, for example, the heat dissipation member is joined to another member such as a semiconductor element by metal plating and brazing material. However, as described above, the aluminum-diamond composite has a cut surface by laser processing. Diamond powder exposed on the cut surface may cause a decrease in adhesion of the metal plating or a decrease in bondability with the brazing material, which may lead to an increase in thermal resistance at the contact interface with the other member.

[0004] Patent Document 1 discloses a method of providing an additional metal layer on the cut surface in order to reduce the influence of the cut surface caused by laser processing or the like. Specifically, the method includes the steps of: preparing a diamond powder in step 1; preparing one or more aluminum-containing materials selected from aluminum-containing ceramics and aluminum-containing metal materials in step 2; filling a cavity of a mold material made of a porous body with the diamond powder layer having aluminum-containing materials on both sides thereof, sandwiching the layer with release plates from above and below, and impregnating the aluminum-containing metal by molten metal casting to produce a plate-shaped aluminum-diamond composite precursor having a surface layer containing 80% or more by volume of the aluminum-containing metal on both sides thereof; and filling a cavity of a mold material made of a porous body with the precursor in a state in which the aluminum-containing material is disposed on all sides of the precursor and release plates are disposed on both sides of the precursor, and impregnating the aluminum-containing metal by molten metal casting to produce a plate-shaped aluminum-diamond composite having a surface layer containing 80% or more by volume of the aluminum-containing metal on all sides thereof. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 158993 Summary of the Invention [Problem to be solved by the invention]

[0006] As the demand for aluminum-diamond composites increases, there is a demand for producing such composites in a shorter time in order to reduce processing costs and improve productivity. There is also a demand for more easily producing aluminum-diamond composites in the shape of products directly, without going through laser processing or the like.

[0007] An object of the present disclosure is to provide a method for producing an aluminum-diamond composite more simply than conventional methods, without requiring laser processing or the like. [Means for solving the problem]

[0008] This disclosure provides the following [1] to

[13] . [1] a step of providing a laminated structure including a composition layer containing diamond powder within an opening of a flat-plate-shaped porous material so as to be spaced from an inner peripheral surface of the opening; and a step of forcing a molten aluminum-containing metal between the porous material and the laminated structure to impregnate the composition layer, thereby forming a composite part containing aluminum and diamond, and forming a metal layer on at least a side surface of the laminated structure. A method for producing an aluminum-diamond composite, wherein the laminated structure comprises, in this order, a first release plate, a first inorganic layer, the composition layer, a second inorganic layer, and a second release plate. [2] The manufacturing method described in [1], wherein the opening is a through hole penetrating in the vertical direction. [3] The manufacturing method described in [1], wherein the opening is a recess. [4] The method according to any one of [1] to [3], wherein the first inorganic layer is at least one of an inorganic fiber-containing layer and a metal foil containing aluminum. [5] The method according to any one of [1] to [4], wherein the second inorganic layer is at least one of an inorganic fiber-containing layer and a metal foil containing aluminum. [6] The manufacturing method according to any one of [1] to [5], wherein the distance between the inner peripheral surface of the opening of the porous material and the laminated structure is 0.05 to 3.50 mm. [7] The manufacturing method according to any one of [1] to [6], further comprising a step of adjusting an average thickness of the metal layer. [8] The manufacturing method according to any one of [1] to [7], wherein the step of forming the metal layer is carried out by a melt casting method. [9] The method according to any one of [1] to [8], wherein the aluminum content in the molten material is 80 mass % or more.

[10] The aluminum-diamond composite has a flat composite part containing aluminum and diamond, a metal-containing layer provided on a pair of main surfaces of the composite part, and a metal layer provided on a side surface of the composite part, and the metal layer has an average thickness of 0.01 to 3.00 mm.

[11] The manufacturing method according to

[10] , wherein the surfaces of the metal-containing layer and the metal layer opposite to the composite portion are smooth surfaces.

[12] The method according to

[11] , wherein the smooth surface has a surface roughness Ra of 0.5 to 1.0 μm.

[13] The method according to any one of

[10] to

[12] , wherein the metal-containing layer has an average thickness of 0.01 to 0.20 mm.

[0009] One aspect of the present disclosure provides a method for producing an aluminum-diamond composite, the method comprising the steps of: providing a laminate structure including a composition layer containing diamond powder within an opening of a flat porous material having an opening, the laminate structure being spaced from the inner peripheral surface of the opening; and forcing a molten metal containing aluminum between the porous material and the laminate structure and impregnating the composition layer to form a composite part containing aluminum and diamond, and forming a metal layer on at least a side surface of the laminate structure, the laminate structure comprising, in this order, a first release plate, a first inorganic layer, the composition layer, a second inorganic layer, and a second release plate.

[0010] In the method for producing the aluminum-diamond composite, the laminate structure is provided with a gap on the inner circumferential surface of the opening of the porous material (for example, the entire periphery of the inner wall when the opening is a through hole), so that the molten metal containing aluminum that is subsequently pressed in spreads over the surface of the laminate structure, thereby directly producing an aluminum-diamond composite having a metal layer containing aluminum on its surface. This eliminates the need for laser processing and requires fewer processing steps, making it possible to produce an aluminum-diamond composite in a shorter time than before.

[0011] In the above-mentioned manufacturing method, when forming the composite part containing aluminum and diamond, a metal layer is formed between the mold and the part, thereby directly manufacturing an aluminum-diamond composite in the shape of a product.

[0012] The opening may be a through hole penetrating in the vertical direction. By using the opening as a through hole, it becomes easier to remove the composite from the mold after the metal layer is formed.

[0013] The opening may be a recess.

[0014] The first inorganic layer may be at least one of an inorganic fiber-containing layer and a metal foil containing aluminum.

[0015] The second inorganic layer may be at least one of an inorganic fiber-containing layer and a metal foil containing aluminum.

[0016] The distance between the inner circumferential surface of the opening of the porous material and the laminated structure may be 0.05 to 3.50 mm.

[0017] The manufacturing method may further include a step of adjusting an average thickness of the metal layer.

[0018] The step of forming the metal layer may be carried out by a melt casting method.

[0019] The aluminum content in the melt may be 80 mass % or more.

[0020] The aluminum-diamond composite obtained by the above-mentioned manufacturing method has a flat composite part containing aluminum and diamond, a metal-containing layer provided on a pair of main surfaces of the composite part, and a metal layer provided on a side surface of the composite part, and the average thickness of the metal layer may be 0.01 to 3.00 mm. By having the average thickness of the metal layer within the predetermined range, the obtained aluminum-diamond composite can also exhibit excellent thermal shock resistance at the joint surface between the composite part and the metal layer.

[0021] The metal-containing layer and the metal layer may have a smooth surface on the side opposite to the composite portion.

[0022] The smooth surface may have a surface roughness Ra of 0.5 to 1.0 μm.

[0023] The metal-containing layer may have an average thickness of 0.01 to 0.20 mm. Effect of the Invention

[0024] According to the present disclosure, it is possible to provide a method for producing an aluminum-diamond based composite more simply than before, without performing laser processing or the like. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a schematic diagram for explaining an example of a method for producing an aluminum-diamond based composite. [Diagram 2] FIG. 2 is a perspective view showing an example of an aluminum-diamond composite. [Diagram 3] FIG. 3 is a cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 4 is a top view showing an example of an aluminum-diamond composite. [Diagram 5]FIG. 5 is a schematic diagram for explaining the measurement method in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings as needed. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.

[0027] Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition unless otherwise specified. In this specification, a range represented by "to" includes an upper limit and a lower limit unless otherwise specified, for example, "X to Y" means "X or more and Y or less."

[0028] One embodiment of the manufacturing method of the aluminum-diamond composite has the steps of: providing a laminated structure containing a composition layer containing diamond powder in the opening of a flat-shaped porous material having an opening, so as to be spaced from the inner peripheral surface of the opening (hereinafter also referred to as a laminated structure laying step); pressing a molten metal containing aluminum between the porous material and the laminated structure, and impregnating the composition layer to form a composite part containing aluminum and diamond, and forming a metal layer on at least the side of the laminated structure (hereinafter also referred to as a metal layer forming step); and adjusting the average thickness of the metal layer (hereinafter also referred to as a layer thickness adjusting step). Note that the layer thickness adjusting step is an optional step and can be omitted. For example, if the average thickness of the metal layer formed by the metal layer forming step is 0.01 to 3.00 mm, the layer thickness adjusting step may be omitted.

[0029] FIG. 1 is a schematic diagram for explaining an example of a method for producing an aluminum-diamond composite. FIG. 1(a) shows a laminated structure laying step, FIG. 1(b) shows a metal layer forming step, and FIG. 1(c) is a schematic cross-sectional view showing an example of an aluminum-diamond composite obtained by the above-mentioned production method. In FIG. 1, the opening of the porous material 50 is a through hole penetrating in the vertical direction. However, the opening may be, for example, a recess having an opening on one main surface side of the porous material 50. In addition, from the viewpoint of obtaining a more homogeneous aluminum-diamond composite 100 as the target, it is desirable to provide one opening at the center of the porous material 50, but there is no particular limitation. For example, a plurality of openings may be provided in one porous material 50, and the position where the opening is formed may also be appropriately adjusted. In the following description, an example will be described in which the opening is a through hole, but when the opening is a recess, it may be read as one of the metal plates 60 in FIG. 1(a) being integral with the porous material 50 using the same material.

[0030] The laminated structure laying step is a step of providing a laminated structure 30 inside an opening of a porous material 50, which is a frame material that is placed between two metal plates 60 and serves as a mold for an aluminum-diamond composite 100, with a gap provided so as to be away from the inner peripheral surface 50a of the opening of the porous material 50. The method of providing the laminated structure 30 inside the opening of the porous material 50 is not particularly limited, but may be, for example, a method of placing the porous material 50 on the metal plate 60, and then sequentially stacking each layer constituting the laminated structure 30, or a method of inserting a separately formed laminated structure 30 inside the opening of the porous material 50. A means of providing a gap (distance g) between the inner peripheral surface 50a of the opening of the porous material 50 and the outer peripheral surface of the laminated structure 30 may be, for example, a method of providing a spacer of a predetermined thickness that can be removed later so as to be in contact with the inner peripheral surface 50a of the opening, forming or inserting the laminated structure 30 inside the spacer (the space on the opposite side to the porous material 50 side), and then removing the spacer. Although FIG. 1 shows an example in which one laminate structure 30 is provided, a plurality of laminate structures 30 may be laminated inside the opening of the porous material 50 along the thickness direction of the porous material 50 .

[0031] The distance g between the inner peripheral surface 50a of the opening of the porous material 50 and the outer peripheral surface of the laminated structure 30 can be adjusted according to the thickness of the metal layer to be formed on the side surface of the target aluminum-diamond composite. The distance g between the inner peripheral surface 50a of the opening of the porous material 50 and the outer peripheral surface of the laminated structure 30 may be, for example, 0.05 to 3.50 mm, 0.05 to 2.50 mm, or 0.05 to 1.00 mm.

[0032] The metal plate 60 may be, for example, an iron plate, a stainless steel plate, or the like.

[0033] The porous material 50 is a heat-resistant porous material that can be pressed or penetrated with a molten metal containing aluminum in the metal layer forming step described later. The porous material 50 may be, for example, a porous sintered body (e.g., an isotropic graphite mold material, etc.) made of graphite or boron nitride, or a porous body made of alumina fibers. The shape of the opening of the porous material 50 can be adjusted according to the shape of the target aluminum-diamond composite 100. In the manufacturing method of the present disclosure, the shape of the aluminum-diamond composite 100 can be changed by adjusting the shape of the opening of the porous material 50, and therefore, unlike the conventional method of forming by laser processing or the like, the manufacturing method has excellent design freedom.

[0034] The laminated structure 30 provided in the laminated structure laying step includes a first release plate 6a, a first inorganic layer 4a, a composition layer 2, a second inorganic layer 4b, and a second release plate 6b, in this order. The first inorganic layer 4a and the second inorganic layer 4b may be the same or different.

[0035] The composition layer 2 may be composed of, for example, only diamond powder, or may contain other components. The other components may be, for example, a binder such as silica. When the composition layer 2 contains other components, the content of the other components may be, for example, 0.5 to 3.0 mass% based on the total amount of the composition layer 2.

[0036] The diamond powder constituting the composition layer 2 may be a powder of natural diamond, a powder of artificial diamond, or a mixture of the two. Diamond particles having a β-type silicon carbide layer formed on the surface may be used as the diamond powder. Such diamond particles can suppress the generation of metal carbides with low thermal conductivity (e.g., aluminum carbide (Al4C3)) when contacted with a melt of a metal containing aluminum in the metal layer forming step described later, and thus can further improve the thermal conductivity of the resulting aluminum-diamond composite 100.

[0037] The diamond powder may have a particle size distribution adjusted from the viewpoint of improving thermal conductivity. The diamond powder preferably has a plurality of peaks in a volumetric particle size distribution curve. Such diamond powder may be a mixed powder of two or more kinds of powders having different average particle sizes. The diamond powder may have, for example, a first peak in a particle size range of 5 to 25 μm and a second peak in a particle size range of 55 to 195 μm in a volumetric particle size distribution curve. The first peak is preferably in a particle size range of 10 to 20 μm. The second peak is preferably in a particle size range of 100 to 180 μm.

[0038] The average particle size in this specification is the particle size (median size, d50) at which the cumulative value of the cumulative particle size distribution is 50%. The average particle size in this specification is measured using a laser diffraction scattering particle size distribution measuring device in accordance with the description of ISO 13320:2009. As the laser diffraction scattering particle size distribution measuring device, for example, "LS-13 320" (device name) manufactured by Beckman Coulter, Inc. can be used.

[0039] The diamond powder preferably contains a relatively large amount of powder having a large particle diameter. In the volumetric particle size distribution curve of the diamond powder, when the area of ​​the region with a particle diameter of 1 to 35 μm is A and the area of ​​the region with a particle diameter of 45 to 205 μm is B, the ratio of B to A (value of B / A) may be, for example, 1.5 or more, 2.3 or more, 4.0 or more, or 9.0 or more. By keeping the value of B / A within the above range, the amount of diamond filling can be improved, and the thermal conductivity of the obtained aluminum-diamond composite 100 can be improved.

[0040] In this specification, the particle size distribution refers to a value measured based on the Coulter method.

[0041] The first inorganic layer 4a and the second inorganic layer 4b may be, independently of each other, for example, at least one of an inorganic fiber-containing layer and a metal foil containing aluminum.

[0042] The inorganic fiber-containing layer is, for example, composed of an inorganic fiber mesh so that a molten metal containing aluminum can be pressed or impregnated in the metal layer forming step described later. The inorganic fiber may be, for example, a metal fiber or a ceramic fiber. The ceramic fiber may be, for example, an alumina fiber, a glass fiber, or the like. The aluminum-containing metal foil may be, for example, an aluminum foil, an aluminum alloy foil, or the like.

[0043] The thicknesses of the first inorganic layer 4a and the second inorganic layer 4b may be, for example, 0.01 mm or more, 0.02 mm or more, or 0.03 mm or more, independently of each other. When the lower limit of the thickness of the first inorganic layer 4a and the second inorganic layer 4b is within the above range, the diamond powder can be more sufficiently prevented from being exposed on the surface of the aluminum-diamond composite 100. The thicknesses of the first inorganic layer 4a and the second inorganic layer 4b may be, for example, 0.20 mm or less, 0.15 mm or less, 0.10 mm or less, 0.08 mm or less, or 0.06 mm or less, independently of each other. When the upper limit of the thickness of the first inorganic layer 4a and the second inorganic layer 4b is within the above range, the thermal conductivity in the thickness direction of the obtained aluminum-diamond composite 100 can be more sufficiently prevented from decreasing. The thicknesses can be adjusted within the above range, and may be, for example, 0.01 to 0.20 mm, or 0.02 to 0.15 mm.

[0044] The thickness of the first inorganic layer 4a and the second inorganic layer 4b in this specification can be measured by a micrometer, and is the arithmetic average value of values ​​measured at five points in the plane. It is desirable that the thickness of the first inorganic layer 4a and the second inorganic layer 4b be the same thickness from the viewpoint of improving the thermal conductivity and the like of the obtained aluminum-diamond composite 100 and suppressing warping of the aluminum-diamond composite 100 due to the difference in thermal expansion coefficient.

[0045] The first release plate 6a and the second release plate 6b can be a plate having a dense structure so that sufficient pressure can be applied when the molten metal containing aluminum is pressed into the composition layer 2 and impregnated in the metal layer forming step described later. The first release plate 6a and the second release plate 6b can be, for example, a stainless steel plate, a ceramic plate, or the like. The main surfaces of the first release plate 6a and the second release plate 6b on the composition layer 2 side may be coated with a release agent or may be subjected to a release treatment. Examples of such release agents include graphite, boron nitride, and alumina. The first release plate 6a and the second release plate 6b can be, for example, a release plate to which a release agent is attached after a coating layer of alumina sol or the like is formed on the main surface on the composition layer 2 side. By using such a release plate, more stable release can be performed, and the main surface of the obtained aluminum-diamond composite 100 can be made smoother.

[0046] In the metal layer forming step, a molten metal containing aluminum is supplied between the porous material 50 and the laminated structure 30 through the porous material 50 to form a composite part containing aluminum and diamond, and a metal layer is formed on at least the side of the laminated structure 30. In the metal layer forming step, in addition to the metal layer 24, the molten metal containing aluminum may penetrate into the inside of the first inorganic layer 4a and the second inorganic layer 4b, or on the main surface of the first inorganic layer 4a and the second inorganic layer 4b on the composition layer 2 side, to form the metal-containing layers 22a, 22b. When the first inorganic layer 4a and the second inorganic layer 4b are composed of an inorganic fiber mesh, the molten metal containing aluminum is impregnated into the mesh in this step, a metal-containing layer is formed, and the composite part and the metal-containing layer are firmly bonded to each other. Furthermore, when the first inorganic layer 4a and the second inorganic layer 4b are metal foils containing aluminum, they themselves constitute a metal-containing layer, and a molten aluminum-containing metal penetrates onto the main surfaces of the first inorganic layer 4a and the second inorganic layer 4b facing the composition layer 2, thereby firmly bonding the composite portion and the metal-containing layer.

[0047] In the metal layer forming step, the method of supplying the molten metal containing aluminum may be, for example, a so-called high pressure forging method in which the molten metal is impregnated into the target under high pressure. From the viewpoint of obtaining an aluminum-diamond composite 100 having a superior thermal conductivity, it is desirable to use a molten metal forging method in the metal layer forming step. The metal layer forming step is carried out, for example, by immersing the laminate prepared in the laminate structure laying step itself in a container filled with the molten material and applying pressure to the molten material. As a result, the molten material permeates through the pores of the porous material 50 and is supplied between the inner peripheral surface 50a of the opening of the porous material 50 and the outer peripheral surface of the laminate structure, and then the molten material permeates into the inside of the composition layer 2, resulting in composite formation.

[0048] The aluminum-containing metal melt may contain, for example, other metals in addition to aluminum. Examples of the other metals include silicon, magnesium, and copper. The other metals preferably contain at least one of silicon and magnesium. By containing the above-mentioned metals in the melt, the melting point of the melt can be lowered, and the melt viscosity during impregnation can be lowered, so that the melt can be sufficiently infiltrated into the gaps formed by the particles of diamond powder in the composition layer 2. This action can further improve the density of the composite part in the obtained aluminum-diamond composite 100. When the melt contains silicon, the melting point can be further lowered, and when the melt contains magnesium, the bond between the composite part and the metal layer can be made stronger.

[0049] When the melt contains other metals in addition to aluminum, the content of the other metals may be 2 to 20 mass %, 2 to 15 mass %, or 5 to 15 mass % based on the total amount of the melt.

[0050] When the composition layer 2 is impregnated with the molten material, it is desirable to heat the laminated structure 30, the porous material 50, and the metal plate 60. The lower limit of the heating temperature may be, for example, 520°C or higher, or 540°C or higher. By setting the lower limit of the heating temperature within the above range, the molten material can be more easily impregnated into the composition layer 2, and the compounding in the metal layer forming step can be more stably performed. The upper limit of the heating temperature may be, for example, 750°C or lower, or 700°C or lower. By setting the upper limit of the heating temperature within the above range, the formation of aluminum carbide (Al4C3) during compounding with aluminum can be more suppressed, and the thermal conductivity of the aluminum-diamond composite 100 can be more improved. The heating temperature may be adjusted within the above range, and can be, for example, 520 to 750°C, or 540 to 700°C.

[0051] The pressure when the molten material is impregnated into the composition layer 2 may be, for example, 20 MPa or more, 30 MPa or more, 40 MPa or more, or 50 MPa or more. By setting the lower limit of the pressure when the molten material is impregnated into the composition layer 2 within the above range, the composite in the metal layer forming step can be more stably performed, and the thermal conductivity of the obtained aluminum-diamond composite 100 can be further improved. The pressure when the molten material is impregnated into the composition layer 2 may be, for example, 150 MPa or less, 100 MPa or less, or 80 MPa or less. The pressure when the molten material is impregnated into the composition layer 2 may be adjusted within the above range, and may be, for example, 20 to 150 MPa.

[0052] In the layer thickness adjustment step, the average thickness of the metal layer 24 is adjusted to 0.01 to 3.00 mm. This step makes it possible to adjust the average thickness, surface roughness Ra, dimensions, dimensional accuracy, etc. of the metal layer. In this step, the average thickness of the metal-containing layers 22a, 22b can also be adjusted as necessary.

[0053] Prior to the layer thickness adjustment step, the metal plate 60 and the porous material 50 are removed, and the first release plate 6a and the second release plate 6b are peeled off from the metal-containing layer 22a and the metal-containing layer 22b, respectively.

[0054] The average thickness of the metal layer 24 can be adjusted by a processing method employed in ordinary metal processing, such as polishing, surface grinding, or the like.

[0055] The above-mentioned manufacturing method may include other steps in addition to the laminated structure laying step, the metal layer forming step, and the layer thickness adjusting step, such as an annealing step and a surface treatment step.

[0056] The annealing step is a step in which the metal layer 24 is formed before the layer thickness adjustment step, and then a heat treatment is performed at a relatively low temperature to reduce distortion that may be present in the composite part 10, the metal layer 24, etc. This step makes it possible to manufacture an aluminum-diamond composite 100 with superior thermal conductivity. The heating temperature in the annealing step may be, for example, 400 to 550°C, or 400 to 500°C. The heating time in the annealing step may be, for example, 10 minutes or more, or 20 minutes or more, and may be 24 hours or less, or 12 hours or less.

[0057] In the manufacturing method according to the present disclosure, the aluminum content in the molten metal containing aluminum may be, for example, 80% by mass or more. In the manufacturing method according to the present disclosure, the aluminum content in each of the metal-containing layer 22a, the metal-containing layer 22b, and the metal layer 24 may be, for example, 80% by mass or more. In this case, processing can be more easily performed by a normal metal processing method such as polishing. The aluminum content described above may be 85% by mass or more, 90% by mass or more, or 95% by mass or more, and the aluminum content in the metal-containing layer 22a and the metal-containing layer 22b may be 100% by mass (i.e., a metal foil made of aluminum).

[0058] Fig. 2 is a perspective view showing an example of an aluminum-diamond composite obtained by the above-mentioned manufacturing method. Fig. 3 is a cross-sectional view taken along line III-III in Fig. 2. The aluminum-diamond composite 102 has a flat composite part 10 containing aluminum and diamond, and a coating layer 20 provided on the surface of the composite part 10. The coating layer 20 has metal-containing layers 22a and 22b provided on a pair of main surfaces of the composite part 10, and a metal layer 24 provided on the side surface of the composite part 10. The aluminum-diamond composite 102 may be the same as the aluminum-diamond composite 100 obtained by the above-mentioned manufacturing method.

[0059] The thickness t1 of the composite portion 10 may be, for example, 0.4 to 6.0 mm, 0.4 to 5.0 mm, or 0.4 to 4.0 mm. When the lower limit of the thickness t1 is within the above range, sufficient strength can be ensured when the aluminum-diamond composite 102 is used, for example, as a heat sink. When the upper limit of the thickness t1 is within the above range, sufficient thermal conductivity can be ensured for the aluminum-diamond composite 102, and an increase in production costs can be suppressed.

[0060] The total thickness (2t2) of the metal-containing layers 22a and 22b constituting both main surfaces of the aluminum-diamond composite 102 may be, for example, 20% or less, 15% or less, or 10% or less based on the thickness T of the aluminum-diamond composite 102. When the total thickness (2t2) of the metal-containing layers 22a and 22b is within the above range, plating properties can be improved while ensuring thermal conductivity.

[0061] The average thickness t2 of the metal-containing layers 22a, 22b provided on both main surfaces of the composite section 10 may be, for example, 0.01 to 0.20 mm, or 0.02 to 0.15 mm. The average thickness t2 of the metal-containing layers 22a, 22b provided on both main surfaces of the composite section 10 can be adjusted by adjusting the thicknesses of the first inorganic layer 4a and the second inorganic layer 4b, or the like.

[0062] The average thickness e of the metal layer 24 on the side surface of the composite part 10 is, for example, 0.01 to 3.00 mm. The average thickness e of the metal layer 24 on the side surface of the composite part 10 can be adjusted by the distance between the inner circumferential surface 50a of the opening of the porous material 50 and the outer circumferential surface of the laminated structure 30 in the above-mentioned manufacturing method of the aluminum-diamond composite, the layer thickness adjustment step, etc.

[0063] 4 is a top view showing an example of an aluminum-diamond composite 102. The average thickness e of the metal layer 24 formed on the side surface of the aluminum-diamond composite 102 can be adjusted to a certain degree in order to further suppress the occurrence of cracks when thermal shock is applied by a heat cycle test or the like. The total value (2e) of the average thicknesses e of the metal layer 24 on both side surfaces of the aluminum-diamond composite 102 may be, for example, 30% or less, 20% or less, 15% or less, or 10% or less based on the external dimension L of the aluminum-diamond composite 102. The external dimension refers to the maximum length of the side of the aluminum-diamond composite 102.

[0064] In the top view of the aluminum-diamond composite 102, when the area of ​​the metal layer 24 is C and the area of ​​the metal-containing layer 22a is D, C may be, for example, 50.0% or less, 40.0% or less, or 30.0% or less based on D. C may also be, for example, 0.1% or more, or 0.5% or more based on D. The area C of the metal layer 24 in the top view of the aluminum-diamond composite 102 (the area of ​​the band-shaped region including the outer edge in the top view of the aluminum-diamond composite 102) may be adjusted within the above-mentioned range, and may be, for example, 0.1 to 50.0% based on the area D of the metal-containing layer 22a in the top view of the aluminum-diamond composite 102.

[0065] In a top view of the aluminum-diamond composite 102, the radius of curvature at the four corners of the metal layer 24 may be, for example, 0.5 mm or more, 0.7 mm or more, or 1.0 mm or more. When the radius of curvature is within the above range, the handleability of the aluminum-diamond composite 102 can be improved, and damage to other members during transportation can also be suppressed. The radius of curvature at the four corners of the metal layer 24 may be, for example, 5.0 mm or less, or 4.0 mm or less.

[0066] At least one of the metal-containing layers 22a, 22b and the metal layer 24 may have a smooth surface on the side opposite to the composite section 10. The metal-containing layers 22a, 22b may have a smooth surface on the side opposite to the composite section 10. The metal layer 24 may have a smooth surface on the side opposite to the composite section 10. The surface roughness Ra of the smooth surface may be, for example, 0.5 to 1.0 μm, or 0.5 to 0.8 μm. When the surface roughness Ra is within the above range, the thermal resistance at the joint surface with another member can be further reduced when the aluminum-diamond composite 100, 102 is used as a heat dissipation member such as a heat sink.

[0067] In this specification, the surface roughness Ra means the arithmetic mean roughness described in JIS B 0601:1994 "Geometrical Product Specifications (GPS)-Surface Texture: Profile Method-Terminology, Definitions and Surface Texture Parameters" and can be measured by a line contact type measuring instrument. For line contact type measurement, for example, the "Surftest SJ-301 Surface Roughness Measuring Instrument" (product name) manufactured by Mitutoyo Corporation can be used.

[0068] The flatness of the metal-containing layers 22a, 22b in the aluminum-diamond composites 100, 102 may be, for example, 0.020 mm or less, or 0.010 mm or less, calculated on a 10 mm×10 mm size. By having the flatness within the above range, it is possible to suppress the variation of the bonding layer in bonding to other members, and to obtain higher heat dissipation properties.

[0069] The lower limit of the aluminum content in the metal layer 24 constituting the aluminum-diamond composite 100, 102 may be, for example, 80 mass% or more, 82 mass% or more, 84 mass% or more, or 86 mass% or more. The upper limit of the aluminum content in the metal layer 24 constituting the aluminum-diamond composite 100, 102 may be, for example, 98 mass% or less, 96 mass% or less, 94 mass% or less, 92 mass% or less, 90 mass% or less, or 88 mass% or less.

[0070] The lower limit of the aluminum content in the metal-containing layers 22a, 22b constituting the aluminum-diamond composites 100, 102 may be, for example, 90 mass% or more, 92 mass% or more, 94 mass% or more, 96 mass% or more, or 98 mass% or more. The upper limit of the aluminum content in the metal-containing layers 22a, 22b constituting the aluminum-diamond composites 100, 102 is not particularly limited and may be 100 mass% (i.e., a layer made of aluminum), but may be, for example, 99 mass% or less.

[0071] In this specification, the aluminum content of the metal-containing layers on both main surfaces and the metal layer on the side surface of the aluminum-diamond composite refers to the value measured by an energy dispersive X-ray analyzer.

[0072] The aluminum-diamond based composites 100, 102 have excellent thermal conductivity. The thermal conductivity of the aluminum-diamond based composites 100, 102 at 25° C. can be, for example, 400 W / mK or more, 450 W / mK or more, or 500 W / mK or more.

[0073] The thermal conductivity in this specification refers to a value measured by a laser flash method. For the measurement, for example, "LF / TCM-8510B" (product name) manufactured by Rigaku Corporation can be used.

[0074] The aluminum-diamond based composites 100 and 102 are suppressed to have a low deformation during heating. The linear expansion coefficient of the aluminum-diamond based composites 100 and 102 when heated from 25° C. to 400° C. is, for example, 5.0×10 -6 ~10.0×10 -6 K -1 , 5.5×10 -6 ~9.0×10 -6 K -1 , or 5.5 × 10 -6 ~8.5×10 -6 K -1 It can be said that:

[0075] The term "linear expansion coefficient" as used herein refers to a value measured using a thermal dilatometer, such as "TMA300" (product name) manufactured by Seiko Instruments Inc.

[0076] The above-mentioned aluminum-diamond composites 100, 102 have excellent thermal conductivity and can be suitably used as heat dissipation members, etc. The aluminum-diamond composite according to the present disclosure has a thermal expansion coefficient equivalent to that of a general semiconductor element, and is therefore useful as a heat dissipation member for a semiconductor element. Here, examples of the semiconductor element include semiconductor laser elements that require high output, such as gallium nitride (GaN), gallium arsenide (GaAs), and silicon carbide (SiC), as well as high-frequency elements such as GaN-HEMT (High Electron Mobility Transistor: HEMT) elements and GaAs-HEMT elements.

[0077] The above-mentioned aluminum-diamond based composites 100, 102 can also be used as a plated part having a plating layer formed thereon. One embodiment of the plated part has a flat aluminum-diamond based composite and a metal plating layer provided on the aluminum-diamond based composite, and the aluminum-diamond based composite is the above-mentioned aluminum-diamond based composite.

[0078] The metal plating layer in the plated part may have a nickel plating layer and a gold plating layer in this order from the aluminum-diamond composite side. In this case, it is preferable that the average thickness of the nickel plating layer is 0.5 to 6.5 μm, and the average thickness of the gold plating layer is 0.5 μm or more. By making the average thickness of the nickel plating layer within the above range, the occurrence of defects such as pinholes in the plating layer can be suppressed, and the occurrence of peeling of the plating film and cracks can be more sufficiently suppressed even in a high-temperature environment when the plated part is used.

[0079] A typical plating method can be used to form the plating layer. Examples of plating methods that can be used include electrolytic plating and electroless plating. When nickel plating is performed on the metal-containing layers 22a and 22b and the metal layer 24, a pretreatment may be performed to replace at least a part of the surface of the aluminum-diamond composites 100 and 102 with zinc or the like. By performing such a pretreatment, the adhesion of the plating layer can be further improved.

[0080] When nickel plating is performed, it is more preferable to further perform an amorphous nickel alloy plating having a thickness of 0.5 to 6.5 μm on the surface. In this case, even if diamond powder is exposed on the surface of the aluminum-diamond composite, the generation of pinholes and the like can be suppressed, so that the means for forming the amorphous nickel alloy plating is preferably an electroless plating method. In this case, the amorphous nickel alloy plating may be an alloy plating containing nickel and phosphorus (P) in an amount of, for example, 5 to 15% by weight.

[0081] In addition, as the bonding temperature rises and the temperature load increases during actual use, the amorphous nickel alloy plating crystallizes, causing microcracks due to the volume change at that time, and the cracks may propagate due to the subsequent temperature load. Therefore, it is preferable that the nickel alloy plating layer has a thickness of, for example, 0.5 μm to 2 μm.

[0082] When used in applications where brazing material is used for joining at high temperatures, it is desirable to provide a gold plating layer on the outermost surface of the plated part. The thickness of the gold plating layer may be, for example, 0.01 μm or more from the viewpoint of sufficiently strong joining. The thickness of the gold plating layer may be, for example, 4.00 μm or less from the viewpoint of reducing costs.

[0083] Although several embodiments have been described above, the descriptions of the embodiments can be applied to each other with respect to common configurations. Furthermore, the present disclosure is not limited to the above-described embodiments. EXAMPLES

[0084] The present disclosure will be described in more detail with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.

[0085] Example 1 A high-purity diamond powder with an average particle size of 130 μm (manufactured by Diamond Innovation Co., Ltd.) and a high-purity diamond powder with an average particle size of 15 μm (manufactured by Diamond Innovation Co., Ltd.) were mixed in a mass ratio of 7:3 to prepare a mixed powder. In addition, alumina sol was coated on the surface of a stainless steel plate (SUS430 material) with dimensions of length: 43.4 mm x width: 43.4 mm x thickness: 2 mm, and baked at 350°C for 30 minutes, after which a graphite-based release agent was applied to the surface to prepare a release plate.

[0086] Next, an isotropic graphite mold material (porosity: 20% by volume) having an outer shape of 80 mm long x 80 mm wide x 5.5 mm thick, and an opening (50.2 mm long x 50.2 mm wide, and a radius of curvature of the four corners of 1.0 mm) penetrating through the thickness direction in the center was prepared on a 12 mm thick iron plate, and a spacer having a thickness of 3.40 mm was placed so as to contact the inner peripheral surface of the opening. In the space surrounded by the spacer, a release plate and pure aluminum foil (aluminum content: 100% by mass, thickness: 0.05 mm, corresponding to the first inorganic layer (later metal-containing layer)) were laminated in this order, and the above-mentioned mixed powder was filled thereon to form a composition layer having a thickness of 2.00 mm. On the above composition layer, pure aluminum foil (aluminum content: 100% by mass, thickness: 0.05 mm, corresponding to the second inorganic layer (later metal-containing layer)) and a release plate were further laminated in this order to provide a laminated structure. After that, the spacer was removed to form a space between the isotropic graphite mold and the laminated structure. After removing the spacer, another iron plate was placed on top to obtain a block-shaped structure (a structure similar to that shown in Figure 1(a) was formed. Laminated structure laying process).

[0087] The block-shaped structure was preheated to 650°C in an electric furnace and then placed in a preheated press mold with an inner diameter of 300 mm. A metal mixture having a composition of 12% by mass of silicon, 1% by mass of magnesium, and 87% by mass of aluminum was melted at 800°C to form a molten material (molten metal), which was poured into the press mold containing the preheated block-shaped structure, and a pressure of 100 MPa was applied for 20 minutes to allow the molten material to penetrate into the interior (metal layer formation process). The metal was then cooled to room temperature. The aluminum content in the molten metal was determined by measuring the metal mixture before melting using solid-state emission spectroscopy.

[0088] After cooling, the isotropic graphite mold was cut slightly inward along the shape of the isotropic graphite mold with a wet band saw, and the iron plate, isotropic graphite mold, and release plate were peeled off. Then, annealing was performed at 450°C for 3 hours to remove distortion caused during impregnation (annealing step). After the annealing, the surface of the annealed product was polished to obtain an aluminum-diamond composite.

[0089] <Measurement of physical properties of aluminum-diamond composite> The resulting aluminum-diamond composite was measured for its outer dimensions, the average thickness of the metal-containing layer and the metal layer, the proportion of the metal layer on the side surface, the aluminum content of the metal layer, and the radius of curvature. The results are shown in Table 1.

[0090] [External dimensions measurements] The outer dimensions of the aluminum-diamond composite were measured using a vernier caliper.

[0091] [Measurement of the average thickness of the metal-containing layer and the metal layer] The thickness of the metal-containing layer on both main surfaces of the aluminum-diamond composite and the metal layer on the side surface were measured as follows. As shown in FIG. 5, the aluminum-diamond composite was cut along the center line of the aluminum-diamond composite (shown by a dashed line in FIG. 5) with a diamond processing tool. Then, at the four ends marked with circles in FIG. 5, images of the cut surface including both main surfaces and the side surface were obtained at 100 times magnification with a scanning electron microscope. The distance from the outermost surface and the side surface to the diamond powder was measured at five points at intervals of 200 μm. The same measurement was performed at four points, and the arithmetic average value was taken as the average thickness of the metal layer.

[0092] [Proportion of metal layer in top view] The proportion of the metal layer in top view was calculated using the following formula from the outer dimensions obtained by the above measurements and the average thickness of the metal layer. Percentage of metal layer in top view = 100 - [(external dimensions) - 2 (average thickness of metal layer)] 2 ÷[External dimensions] 2 ×100

[0093] [Measurement of aluminum content in metal-containing layer and metal layer] The aluminum contents of the metal-containing layers on both main surfaces of the aluminum-diamond composite and the metal layers on the side surfaces were measured by an energy dispersive X-ray analyzer.

[0094] [Measurement of radius of curvature] The radii of curvature at the four corners of the aluminum-diamond composite were measured by a CNC (Computer Numerical Control) image measuring machine.

[0095] <Evaluation of aluminum-diamond composite> The aluminum-diamond composite was evaluated for the presence or absence of chipping on the periphery and for thermal shock resistance according to the methods described below. The results are shown in Table 1.

[0096] [Presence or absence of chipping on the periphery] The side of the aluminum-diamond composite was observed under a 10x stereomicroscope immediately after the iron plate, isotropic graphite mold material, and release plate were removed, and the results were evaluated according to the following criteria. A: There are no chips with a diameter of 100 μm or more in the metal layer mainly composed of aluminum on the entire outer periphery, including the four corners. B: One or more chips with a diameter of 100 μm or more have occurred in the metal layer mainly composed of aluminum over the entire outer periphery, including the four corners.

[0097] [Thermal shock resistance] A heat cycle test was performed on the aluminum-diamond composite under the following conditions. Specifically, the aluminum-diamond composite was exposed to a gas phase held at -40°C for 30 minutes, and then to a gas phase held at 125°C for 30 minutes. This cycle was repeated 100 times. The surface of the composite was then observed using a stereo microscope with a magnification of 10x and an ultrasonic flaw detector, and the results were evaluated according to the following criteria. A: No cracks were found at the interface between the composite part and the metal layer, either by microscopic observation or ultrasonic testing. B: Cracks were confirmed at the interface between the composite part and the metal layer by either microscopic observation or ultrasonic testing.

[0098] (Examples 2 to 8) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the distance between the inner circumferential surface of the opening and the outer circumferential surface of the laminated structure was changed as shown in Table 1.

[0099] (Examples 9 to 11) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the size of the opening of the porous material was changed and the distance between the inner surface of the opening and the outer surface of the laminated structure was changed as shown in Table 1.

[0100] (Examples 12 and 13) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the distance between the inner surface of the opening and the outer surface of the laminated structure was changed as shown in Table 1, and aluminum alloy foils were used for the first metal foil and the second metal foil.

[0101] (Examples 14 and 15) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the distance between the inner surface of the opening and the outer surface of the laminated structure was changed as shown in Table 1, and the aluminum content in the molten metal was changed.

[0102] Example 16 An aluminum-diamond composite was produced in the same manner as in Example 1, except that a release plate and alumina fiber (thickness: 0.05 mm, porosity: 90%, corresponding to the first inorganic layer) were laminated in that order in the space surrounded by the spacer, and then alumina fiber (thickness: 0.05 mm, porosity: 90%, corresponding to the second inorganic layer) and a release plate were further laminated in that order on top of the composition layer formed on top of them to form a laminated structure.

[0103] (Example 17) The aluminum-diamond based composite of Example 17 was produced by subjecting the metal layer of the aluminum-diamond based composite obtained in Example 1 to surface grinding.

[0104] (Example 18) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the thickness of the pure aluminum foil laminated in the space surrounded by the spacer was changed to 0.01 mm.

[0105] (Example 19) An aluminum-diamond composite was produced in the same manner as in Example 1, except that the thickness of the pure aluminum foil laminated in the space surrounded by the spacer was changed to 0.2 mm.

[0106] Comparative Example 1 An aluminum-diamond based composite was produced in the same manner as in Example 1, except that the distance between the inner peripheral surface of the opening and the outer peripheral surface of the laminated structure was changed as shown in Table 1. As a result, an aluminum-diamond based composite having no metal layer on the side surface was obtained.

[0107] Comparative Example 2 An aluminum-diamond composite was produced in the same manner as in Example 1, except that the distance between the inner circumferential surface of the opening and the outer circumferential surface of the laminated structure was changed to 4.0 mm.

[0108] Comparative Example 3 An aluminum-diamond composite was produced in the same manner as in Example 1, except that the size of the opening of the porous material was changed and the distance between the inner surface of the opening and the outer surface of the laminated structure was changed as shown in Table 1.

[0109] <Measurement of physical properties of aluminum-diamond composite> For each of the aluminum-diamond composites produced in Examples 2 to 19 and Comparative Examples 1 to 3, the external dimensions, the average thickness of the metal-containing layer and the metal layer, the proportion of the metal layer on the side surface, the aluminum content of the metal layer, and the radius of curvature were measured in the same manner as in Example 1. The results are shown in Tables 1 and 2. In Comparative Example 2, powder leakage occurred from the composition layer during production, and a good aluminum-diamond composite could not be produced. Therefore, it was excluded from the evaluation.

[0110] <Evaluation of aluminum-diamond composite> The aluminum-diamond composites prepared in Examples 2 to 15 and Comparative Examples 1 and 3 were evaluated for the presence or absence of chipping on the periphery and for thermal shock resistance in the same manner as in Example 1. The results are shown in Table 1. The aluminum-diamond composite prepared in Comparative Example 1 did not have a metal layer on the side, so it was not possible to judge the thermal shock test. Therefore, it was excluded from the evaluation. In Comparative Example 2, powder leakage occurred from the composition layer during the production, and a good aluminum-diamond composite could not be produced. Therefore, it was excluded from the evaluation.

[0111] [Table 1]

[0112] [Table 2] [Industrial Applicability]

[0113] According to the present disclosure, it is possible to provide a method for producing an aluminum-diamond based composite more simply than before, without performing laser processing or the like. [Explanation of symbols]

[0114] 2...composition layer, 4a...first inorganic layer, 4b...second inorganic layer, 6a...first release plate, 6b...second release plate, 10...composite portion, 20...coating layer, 22a, 22b...metal-containing layer, 24...metal layer, 30...laminated structure, 50...porous material, 50a...inner surface of opening, 60...metal plate, 100, 102...aluminum-diamond composite.

Claims

1. a step of providing a laminated structure including a composition layer containing diamond powder within an opening of a flat-plate-shaped porous material so as to be spaced from an inner peripheral surface of the opening; and pressing a molten aluminum-containing metal into a space between the porous material and the laminated structure to impregnate the composition layer, thereby forming a composite part containing aluminum and diamond, and forming a metal layer on at least a side surface of the laminated structure. The method for producing an aluminum-diamond composite, wherein the laminated structure comprises, in this order, a first release plate, a first inorganic layer, the composition layer, a second inorganic layer, and a second release plate.

2. The manufacturing method according to claim 1 , wherein the opening is a through hole extending in the vertical direction.

3. The method of claim 1 , wherein the opening is a recess.

4. The method according to any one of claims 1 to 3, wherein the first inorganic layer is at least one of an inorganic fiber-containing layer and a metal foil containing aluminum.

5. The method according to claim 1 or 2, wherein the second inorganic layer is at least one of an inorganic fiber-containing layer and a metal foil containing aluminum.

6. 3. The method according to claim 1, wherein the distance between the inner circumferential surface of the opening of the porous material and the laminated structure is 0.05 to 3.50 mm.

7. The method according to claim 1 or 2, further comprising the step of adjusting an average thickness of the metal layer.

8. The method according to claim 1 or 2, wherein the step of forming the metal layer is carried out by a molten metal casting method.

9. The method according to claim 1 or 2, wherein the aluminum content in the molten material is 80 mass% or more.

10. The manufacturing method according to claim 1 or 2, wherein the aluminum-diamond based composite has a flat composite part containing aluminum and diamond, a metal-containing layer provided on a pair of main surfaces of the composite part, and a metal layer provided on a side surface of the composite part, and the average thickness of the metal layer is 0.01 to 3.00 mm.

11. The method according to claim 10 , wherein the metal-containing layer and the metal layer have smooth surfaces on the opposite sides to the composite portion.

12. The manufacturing method according to claim 11, wherein the smooth surface has a surface roughness Ra of 0.5 to 1.0 μm.

13. The method of claim 10, wherein the metal-containing layer has an average thickness of 0.01 to 0.20 mm.

14. The composition layer may contain the diamond powder and other components, The method for producing an aluminum-diamond composite according to any one of claims 1 to 3, wherein the content of the other components in the composition layer is 3.0 mass% or less based on the total amount of the composition layer.

15. The method for producing an aluminum-diamond composite according to claim 1, wherein the composition layer is made of the diamond powder.

16. A method for producing an aluminum-diamond composite as described in any one of claims 1 to 3, wherein the step of forming the metal layer is a step of forcing a molten metal containing aluminum into the space between the porous material and the laminated structure, and impregnating the composition layer to form a composite part containing aluminum and diamond, forming a metal layer on a side of the laminated structure, and joining the first inorganic layer and the second inorganic layer to the composite part, and forming a metal-containing layer on a pair of main surfaces of the composite part.

Citation Information

Patent Citations

  • Aluminum-diamond composite and method for production thereof

    JP2012158817A

  • Composite substrate for LED light emitting element, method of production of same, and LED light emitting element

    WO2010092972A1

  • Aluminum-diamond composite and method for producing same

    WO2017065139A1

  • Aluminum-diamond-based composite and heat dissipation component

    WO2017158993A1